Efficacy of therapies for post dural puncture headache - Thon, Jan Niklas; Weigand, Markus A.; Kranke, Peter; Siegler, Benedikt Hermann (Current opinion in anaesthesiology, 2024)
Purpose of review - Clinical management of postdural puncture headache (PDPH) remains an interdisciplinary challenge with significant impact on both morbidity and quality of life. This review aims to give an overview of the most recent literature on prophylactic and therapeutic measures and to discuss novel findings with regard to currently published consensus practice guideline recommendations. - Recent findings - Although current evidence does not support a recommendation of any specific prophylactic measure, new data is available on the use of intrathecal catheters to prevent PDPH and/or to avoid invasive procedures. In case of disabling or refractory symptoms despite conservative treatments, the epidural blood patch (EBP) remains the therapeutic gold standard and its use should not be delayed in the absence of contraindications. However, recent clinical studies and meta-analyses provide additional findings on the therapeutic use of local anesthetics as potential noninvasive alternatives for early symptom control. - Summary -There is continuing research focusing on both prophylactic and therapeutic measures offering promising data on potential alternatives to invasive procedures, although there is currently no treatment option that comes close to the effectiveness of an EBP. A better understanding of PDPH pathophysiology is not only necessary to identify new therapeutic targets, but also to recognize patients who benefit most from current treatments, as this might enhance their therapeutic efficacy.